The effect of tabletop role-playing games on the creative potential and emotional creativity of Taiwanese college students. (March 2016) - Dyson, Scott Benjamin; Chang, Yu-Lin; Chen, Hsueh-Chih; Hsiung, Hsiang-Yu; Tseng, Chien-Chih; Chang, Jen-Ho
Highlights: This study is the first to use an Asian student sample to investigate the impact of TRPGs on creativity that uses a control. The experimenter remained aloof to isolate the effect of TRPGs from instructional skill. The results of this study lead to the conclusion that TRPGs have a positive effect on cognitive creativity. This study included emotional creativity in its experiment, though the effect was not significant. Abstract: Research on the effect of tabletop role-playing games (TRPGs) on creative potential and emotional creativity has been sparse. The present study aimed to examine how role-playing games influence creative potential and emotional creativity. Participants were assigned into either a treatment group ( N  = 19) or a control group ( N  = 20). After taking the Emotional Creativity Index (ECI) and Abbreviated Torrance Test for Adults (ATTA) as pre-tests, the treatment group played TRPGs once every week for four weeks. Upon the completion of the treatment, the participants retook the tests. The control group only took the pre-tests and post-tests and did not play any role-playing games. The results showed treatment group significantly enhance their creative potential as compared with the control group, but not on emotional creativity. The current study supports that TRPGs improve creative potential, implications and limitations are discussed.